Entrepreneurial Passion to Entrepreneurial Behavior: Role of Entrepreneurial Alertness, Entrepreneurial Self-Efficacy and Proactive Personality - Li, Cai; Murad, Majid; Shahzad, Fakhar; Khan, Muhammad Aamir Shafique; Ashraf, Sheikh Farhan; Dogbe, Courage Simon Kofi (Frontiers in Psychology, 2020)
This study investigated the role of entrepreneurial passion in recognition of opportunity, developing entrepreneurial self-efficacy, and entrepreneurial intention, in the shaping of entrepreneurial actions in the presence of proactive personality. This study applied a partial least squares structural equation modeling (PLS-SEM) to test the hypotheses on a sample of 346 university students from Jiangsu province China. The output of the study showed that entrepreneurial passion positively and significantly influenced entrepreneurial alertness, entrepreneurial self-efficacy to entrepreneurial intention, and entrepreneurial behavior. The findings also showed that a proactive personality positively and significantly moderated the relationship between entrepreneurial intention and entrepreneurial behavior.